Revealing Public Accountability For Village Financial Management Based On Community Partnership Foundations In Pematang Serai Village, Langkat District - Dito Aditia Darma Nasution; Mustafa, Mustafa; Annisa Fajariah Damanik (International Journal of Economic Research and Financial Accounting, 2024)
This research aims to find out how accountable financial management is villages implemented by the government of Pematang Serai Village, Langkat District as well to find out how community empowerment is carried out by the Village government Pematang Serai, Langkat District. This study used qualitative research methods. The data collection technique used in this research is the observation method, interviews and documentation. The data analysis technique used in this research is qualitative data analysis techniques. The data analysis components used are data reduction, data display, and conclusion drawing. The results of the research conducted stated that the financial management stage carried out by Pematang Serai Village has been carried out in accordance with Permendagri No. 20 In 2018.